Caracterización de los sólidos generados en la planta de tratamiento de aguas residuales de palandacocha, mediante análisis físico, químico y microbiológico, para proponer un plan de manejo ambiental - Terán Martínez, Andrés Darío (2016)
The generation of waste sludge has now become an environmental problem that allows us to apply viable criteria of management and disposal of these types of waste previously conditioned, due to its high content of organic matter and other elements such as heavy metals that can grant the Characteristics. The physical-chemical composition of the sludge generated in the treatment of domestic wastewater of the city of Tena that arrives at the WWTP of Palandacocha observing that they are under the permissible limits of the Ecuadorian norm with the exception of the element Zinc whose norm passes of the value of the Permissible limit that is 200 mg-kg-1, at 852.5 mg-kg-1. It is possible to appreciate the values of microbiological concentrations such as fecal coliforms and total coliforms are under the permissible limits of the Ecuadorian norm, on the other hand the content of Nitrogen, Phosphorus and Potassium, show that the percentages contained in the biosolid are relatively Acceptable, so that they are constituted from the optimum agronomic point of view to be used as soil amendments, but first they must be treated by the composting processes. A PM is proposed in order to mitigate and contribute with a technical instrument to generate benefits from the residual sludge generated by the WWTP. This WFP is made up of community relations programs with a budget of USD 6,864, communication, training and environmental education program with a budget of USD 13,651, management program for sludge generated at the GADMT Treatment Plant to generate fertilizer with a Budget of USD 22,506 and the monitoring and tracking program with a budget of USD13,805, totaling USD 56,826.